THE INFLUENCE OF INCOME AND EDUCATION OF CAP TIKUS FARMING COMMUNITIES ON THE CONTINUITY OF CHILDREN'S EDUCATION IN RAANAN BARU VILLAGE, WEST MOTOLING DISTRICT - Gian Ferdinan Johanes Wowor; Henry J. D. Tamboto; Rommy J. R. Mottoh (J-Shelves of Indragiri (JSI), 2026)
This study aims to analyze the influence of income and education levels of cap tikus farmers on the continuity of children’s education in Raanan Baru Village, West Motoling District, South Minahasa Regency. The background of this research is based on the low level of education and unstable income of farming communities, which are suspected to affect children’s educational continuity. The study employed a quantitative approach with an associative research design. The sample consisted of 92 respondents selected through simple random sampling. Data were collected using questionnaires that had been tested for validity and reliability, while data analysis was conducted using multiple linear regression with the assistance of SPSS version 25. The results showed that partially, community income had a positive and significant effect on the continuity of children’s education, while the education level of the community had a positive but insignificant effect. Simultaneously, both variables significantly affected the continuity of children’s education with a coefficient of determination contribution of 63%. These findings emphasize that family economic welfare and parental education are important factors in supporting the continuity of children’s education in rural areas. Therefore, increasing income and educational awareness in the community should become a priority in regional development policies.